The golden door - Rodda, Emily (Rodda, Emily. Three doors trilogy, 2012)
At night the skimmers fly over the Wall looking for human prey and the people of Weld huddle in their houses, but after his two brothers set out through the magic doors in an attempt to find the Enemy and don't come back, young Rye knows that he must follow and find them.